2021
DOI: 10.1177/02676591211006619
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute renal injury and in-hospital mortality in adult patients with postcardiotomy cardiogenic shock requiring veno-arterial extracorporeal membrane oxygenation: utility of MELD-XI score

Abstract: Background: The suitability of model for end-stage liver disease excluding international normalized ratio (MELD-XI) score to predict the incidence of acute kidney injury (AKI) and in-hospital mortality in adult patients with postcardiotomy cardiogenic shock (PCS) requiring venoarterial extracorporeal membrane oxygenation (VA ECMO) remains uncertain. This study was performed to explore whether the MELD-XI score has the association with the incidence of AKI and in-hospital mortality in these patients. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The time of ECMO implantation (intraoperatively or postoperatively) was significantly different between the two groups (82.1% vs. 61.3%, p = 0.011). Previous studies have reported that age, lactate and ejection fraction (EF) may be risk factors for the poor outcome of patients receiving VA ECMO after PCS [ 6 , 8 ]. Age, cross-clamp time, CPB time, the timing of ECMO implantation, mean artery pressure (MAP), lactate concentration before ECMO, and preoperative EF were entered into multivariable logistic regression analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time of ECMO implantation (intraoperatively or postoperatively) was significantly different between the two groups (82.1% vs. 61.3%, p = 0.011). Previous studies have reported that age, lactate and ejection fraction (EF) may be risk factors for the poor outcome of patients receiving VA ECMO after PCS [ 6 , 8 ]. Age, cross-clamp time, CPB time, the timing of ECMO implantation, mean artery pressure (MAP), lactate concentration before ECMO, and preoperative EF were entered into multivariable logistic regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The survival rate has fluctuated between 20.8% and 65.4% amongst various centers with complications including strokes, acute kidney injury (AKI), bleeding, and thrombotic events [ 3 , 4 , 5 ]. AKI requiring continuous renal replacement therapy (CRRT) is particularly common in patients with PCS supported with VA ECMO, which negatively effects survival [ 3 , 5 , 6 ]. Identifying and managing risk factors for AKI will help decrease the incidence of AKI in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms of renal complications in patients with AFM receiving VA-ECMO support are complicated and multifactorial including patient-related factors, MV related factors, ECMO-related factors and so on. Prior to ECMO initiation, hemodynamic instability, low cardiac output [ 14 , 34 ], hypoxemia [ 35 ], inflammatory cytokines [ 36 ] and other illness-related factors [ 37 , 38 ], alone or in combination, contribute to renal dysfunction. MV is widely used in patients with cardiogenic shock for the management of acute hypoxemia, increased work of breathing, airway protection, and hemodynamic or electric instability [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Putting BUN into the risk stratification model of CS may add the model's accuracy. Finally, we believe monitoring BUN can help optimize management strategies, such as predicting the risk of continuous renal replacement therapy (RRT) because studies have shown elevated baseline BUN was associated with increased risk of AKI in patients with postcardiotomy CS [ 33 ]. Recently, Gaudry et al [ 34 ] found in severe AKI patients' BUN concentration higher than 112 mg/dL (39.87 mmol/L) would mandate immediate RRT and longer postponing of RRT initiation did not confer an additional benefit and was associated with potential harm.…”
Section: Discussionmentioning
confidence: 99%